2022
DOI: 10.1038/s41598-022-17449-9
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing revealed comparable frequencies of RNF43 and BRAF mutations in Middle Eastern colorectal cancer

Abstract: Mutation-induced activation of Wnt-β Catenin signaling pathway is frequent in CRC. The E3 ubiquitin ligase, RNF43, has been reported to negatively regulate the Wnt signaling pathway and RNF43 mutations are frequently seen in CRC. However, its role in Middle Eastern CRC remains unclear. Therefore, we employed Exome and Sanger sequencing technology to assess the frequency of RNF43 mutations and its association with other clinico-pathological features in Middle Eastern CRC. RNF43 mutations were found in 5.9% (13/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…A loss of MMR proteins introduces replication errors, mostly in the microsatellites region. [ 15 19 20 ] The seven G tandem repeats involving codon 659 of the RNF43 gene make this region highly error-prone and more reliant on proficient MMR protein functioning, and so, as anticipated, we observed a greater frequency of the p.G659fs alteration in tumors showing loss in MMR protein staining. In our study, a co-loss of MLH1 and PMS2 was observed in two of the four patients harboring the p.G659fs variant.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…A loss of MMR proteins introduces replication errors, mostly in the microsatellites region. [ 15 19 20 ] The seven G tandem repeats involving codon 659 of the RNF43 gene make this region highly error-prone and more reliant on proficient MMR protein functioning, and so, as anticipated, we observed a greater frequency of the p.G659fs alteration in tumors showing loss in MMR protein staining. In our study, a co-loss of MLH1 and PMS2 was observed in two of the four patients harboring the p.G659fs variant.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have associated RNF43 p.G659fs mutations with right-sided CRC and an aggressive phenotype. [ 19 22 23 ] In our study, three of the four mutant cases had right-side tumor location and favorable survival outcomes. Ethnic disparities and differences in the patient inclusion criteria, as well as the small sample size of our study, could be possible reasons for these discrepancies in results.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…UPS dysregulation due to E3-related genes (E3RGs) mutations is strongly associated with poor cancer survival (Seeler and Dejean, 2017). In Colon Cancer pathogenesis, emerging studies have found the critical role of E3-related proteins, such as ZNF280A (Tian et al, 2022, 14), TMEM100 (Zheng et al, 2022), RNF43 (Schatoff et al, 2017;Siraj et al, 2022), and TRIM52 (Guo et al, 2022). Additionally the E3 ligases, RNF128 (Zhuang et al, 2022, 128) and TRIM29 (Jiang et al, 2021) have been reported in the regulation of PI3K/Akt pathway in colorectal cancer.…”
mentioning
confidence: 99%